2018
DOI: 10.1007/s13300-018-0420-6
|View full text |Cite
|
Sign up to set email alerts
|

Combination Treatment of SGLT2 Inhibitors and GLP-1 Receptor Agonists: Symbiotic Effects on Metabolism and Cardiorenal Risk

Abstract: IntroductionWhen treating type 2 diabetes, drugs that cause hypoglycemia and weight gain should, if possible, be avoided. In addition, due to the increased incidence and prevalence of cardiovascular disease, cardiac events and heart failure, as well as the accelerated renal decompensation that may occur with type 2 diabetes, hypoglycemic agents that have the potential to lower cardiac and renal risk should be utilized as early as possible in the course of the disease.MethodsThis is a literature review of the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 33 publications
3
32
0
Order By: Relevance
“…41 Clearly, a targeted therapy for AEC is needed, one that integrates mechanism of action of drugs with the clinical impact of these medications on AEC bleeding. 42,43 Our in vitro findings are consistent with earlier studies that have shown increased VEGF and basic fibroblast growth factor expression in human colonic AEC along with increased VEGF in circulating plasma. 44,45 In this study, we observed increased VEGFA expression in the involved (AEC) tissue, whereas expression of HIF1α was increased in noninvolved tissue (tissue surrounding the AEC).…”
Section: Discussionsupporting
confidence: 91%
“…41 Clearly, a targeted therapy for AEC is needed, one that integrates mechanism of action of drugs with the clinical impact of these medications on AEC bleeding. 42,43 Our in vitro findings are consistent with earlier studies that have shown increased VEGF and basic fibroblast growth factor expression in human colonic AEC along with increased VEGF in circulating plasma. 44,45 In this study, we observed increased VEGFA expression in the involved (AEC) tissue, whereas expression of HIF1α was increased in noninvolved tissue (tissue surrounding the AEC).…”
Section: Discussionsupporting
confidence: 91%
“…For example, the incidence of MACE in the placebo group of the SGLT2i studies is higher than that of the GLP-1a studies, generating substantial, non-statistically scalable heterogeneity. The combination of GLP-1RAs and SGLT2i is an exciting speculation for the future, as this combined therapy may produce additive cardiovascular benefits in patients with T2DM [155]. The development of other peptide hormones that stimulate insulin secretion and regulate appetite is promising, such as dual co-agonists developed in a single molecule, the stimulation of both the GLP-1 and peptide-YY receptor pathways and the co-administration of glucagon and GLP-1 [42].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…The effects of SGLT2 inhibitors and GLP-1 receptor agonists are favourable in patients with T2DM and various cardiovascular risk factors. As these agents exert their antihyperglycaemic and cardiovascular protective effects via different mechanisms, combination therapy is expected to provide additive effects over those achieved with either agent as monotherapy or in combination with other glucose-lowering agents [ 14 16 ].…”
Section: Introductionmentioning
confidence: 99%